2010
DOI: 10.1128/jvi.02743-09
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interactions between the Major and Minor Envelope Proteins of Equine Arteritis Virus Determine Its Tropism for Equine CD3+T Lymphocytes and CD14+Monocytes

Abstract: Extensive cell culture passage of the virulent Bucyrus (VB) strain of equine arteritis virus (EAV) to produce the modified live virus (MLV) vaccine strain has altered its tropism for equine CD3 ؉ T lymphocytes and CD14 ؉ monocytes. The VB strain primarily infects CD14 ؉ monocytes and a small subpopulation of CD3 ؉ T lymphocytes (predominantly CD4 ؉ T lymphocytes), as determined by dual-color flow cytometry. In contrast, the MLV vaccine strain has a significantly reduced ability to infect CD14؉ monocytes and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…This position is a part of the ectodomain of the GP4 protein and was previously described as a variable (3). As GP4 is one of the proteins important for the determination of viral tropism, stable substitution of this nature on the exposed part of this protein could be the result of adaptive pressure (11).…”
Section: Discussionmentioning
confidence: 99%
“…This position is a part of the ectodomain of the GP4 protein and was previously described as a variable (3). As GP4 is one of the proteins important for the determination of viral tropism, stable substitution of this nature on the exposed part of this protein could be the result of adaptive pressure (11).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, both T-lymphocytes and cells of the monocyte/macrophage lineage were found to be infected with EAV. Other studies have also demonstrated that EAV can infect CD3 + T lymphocytes in PBMC in vitro [25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, peripheral blood mononuclear cells (PBMCs) were collected from long-term carrier (n ϭ 7) and noncarrier (n ϭ 7) stallions ( Table 1). The susceptible or resistant phenotype of each animal was defined by dual-color flow cytometric analysis of in vitro EAV-infected CD3 ϩ T lymphocytes as described previously (6). Interestingly, CD3…”
mentioning
confidence: 99%
“…The percentage of the CD3 ϩ T lymphocyte population that was susceptible to EAV infection ranged from 4% to 17% among carrier stallions. As previously described, a majority of the CD3 ϩ T lymphocytes infected which is associated with CD3 ϩ T cell susceptibility, is highlighted in yellow, as described elsewhere (6). Each haplotype is highlighted with a different color.…”
mentioning
confidence: 99%